Interaction of Laurentide and Cordilleran ice in the Beaver Mines area, southwestern Alberta - Holme, Philip; Hicock, Stephen; Jackson, Lionel (Géographie physique et Quaternaire, 2000)
AbstractSurficial geology mapping of the Beaver Mines area, distribution of Canadian Shield erratics, stratigraphy of Quaternary sediments exposed along the Castle River valley and its tributaries and correlation with southwestern Alberta geochronology, indicate that Cordilleran and Laurentide ice were in contact in the lower Castle River valley during the Late Wisconsinan Substage. During this time two Cordilleran glacial advances are recognised in the lower reaches of the valley, its tributaries and the western Interior Plains: 1) an earlier advance (M1), during which ice thickness averaged between 320 - 350 m thick in the Beaver Mines area, and 2) a later readvance (M2). A single Laurentide advance (C2) into the Beaver Mines area was contemporaneous with retreat of Cordilleran ice from the M2 maximum position, resulting in coalescence of the two ice masses. This followed a C1 advance that is recognised outside the area. During montane advances, glaciers were topographically-controlled and efficiently eroded their substrates. Deglaciation was characterised by ice retreat, stagnation of detached ice masses, and damming of glacial lakes by retreating Laurentide ice.